STUDI RIAP CEMPAKA Elmerrillia ovalis (Miq.) Dandy DI PINARAS DAN MASARANG - Zulfitri Lawe; Josephus I. Kalangi; Alfonsius Thomas; Johan A. Rombang (Universitas Sam Ratulangi, 2014)
ABSTRACCommunity forests around Masarang and Pinaras are dominated by stands of E. ovalis (Miq.) Dandy. Theincrement is usually used to express the of increase of stand volume in a specified time unit. This study is aimedto determine the average annual increment of E. ovalis in community forests of Masarang and Pinaras. Thisresearch was conducted in the villages of Masarang and Pinaras. The method used was the comparison of twoindependent samples in two different locations with three replications. The method used was the diameter andheight was measured on 198 E. ovalis trees in Pinaras and 251 E. ovalis trees in Masarang. The results of theanalysis concluded that there was no difference between the increments for E. ovalis in Masarang and Pinaras.Soil fertility, soil texture, and altitude in the 2 locations did not become prohibitive factors for the growth of E.ovalis.Keyword: E. ovalis, Increament, Pinaras, Masarang